2016
DOI: 10.1038/nn.4247
|View full text |Cite
|
Sign up to set email alerts
|

Explicit information for category-orthogonal object properties increases along the ventral stream

Abstract: Extensive research has revealed that the ventral visual stream hierarchically builds a robust representation for supporting visual object categorization tasks. We systematically explored the ability of multiple ventral visual areas to support a variety of 'category-orthogonal' object properties such as position, size and pose. For complex naturalistic stimuli, we found that the inferior temporal (IT) population encodes all measured category-orthogonal object properties, including those properties often conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
307
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(355 citation statements)
references
References 54 publications
39
307
3
Order By: Relevance
“…A possible scenario is that the foveal cortex represents the object category and orientation information at different spatial scales, with the object category and orientation information primarily supported at fine and coarse scales, respectively. Using multielectrode recordings from passively fixating macaques, Hong et al (22) recently showed that "category-orthogonal" features of an object, such as orientation, could be linearly decoded from high-level object areas in the ventral stream, and that this information was likely available on a feedforward pass. At one level, our imaging results are consistent in that we found that LOC was sensitive to the category-orthogonal feature of image orientation; however, this was only for stimuli that were in the same category.…”
Section: Discussionmentioning
confidence: 99%
“…A possible scenario is that the foveal cortex represents the object category and orientation information at different spatial scales, with the object category and orientation information primarily supported at fine and coarse scales, respectively. Using multielectrode recordings from passively fixating macaques, Hong et al (22) recently showed that "category-orthogonal" features of an object, such as orientation, could be linearly decoded from high-level object areas in the ventral stream, and that this information was likely available on a feedforward pass. At one level, our imaging results are consistent in that we found that LOC was sensitive to the category-orthogonal feature of image orientation; however, this was only for stimuli that were in the same category.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in anatomical coverage, experimental design, stimuli, and task render their findings difficult to integrate with previous studies showing that facial identity information is present in ventral regions including FFA (Nestor et al, 2011;Anzellotti et al, 2014) and more anterior temporal regions (Kriegeskorte et al, 2007). Jeong and Xu (2016) argue that the ventral face-identity information that these previous studies found may be due to low-level stimulus confounds, or that face-identity information may be present only in anterior temporal cortex, from which their MRI slice coverage precluded measurement.…”
Section: Review Of Jeong and Xumentioning
confidence: 74%
“…Consistent with this proposal is evidence that, in both humans and monkeys, neural activity in the ventral stream contains information about visual object identity and category (Kriegeskorte et al, 2008;Bell et al, 2009) without being modulated by image properties such as object position, viewing angle, size, or context (Li et al, 2009;Rust and DiCarlo, 2010;Anzellotti et al, 2014). However, other evidence suggests that simple visual features (e.g., motion direction) required to categorize stimuli are also represented in dorsal regions (Toth and Assad, 2002;Freedman and Assad, 2006).…”
Section: Review Of Jeong and Xumentioning
confidence: 96%
See 2 more Smart Citations